The Effects of Stellar Wind, Rotation Velocity, and Overshoot Parameters on The Evolution of Massive Stars using MESA: Case Study of MPG 324, MPG 355, MPG 682 - Alin Hafizhah Adira; Aprilia (Spektra: Jurnal Fisika dan Aplikasinya, 2024)
Massive stars (over 8 solar masses) undergo intricate cosmic journeys. Their evolution, shaped by parameters like stellar wind, rotation velocity, and overshoot, generally includes the pre-main sequence, main sequence, and post-main sequence phases. In the post-main sequence, they become supergiant stars, then Wolf-Rayet stars, experience a supernova, and end as neutron stars or black holes. This study models the evolutionary path of massive stars using MESA software, considering stellar wind, rotation velocity, and overshoot. Three stars from the Small Magellanic Cloud galaxy—MPG 324, MPG 355, and MPG 682—are used to represent the mass range described in the Conti Scenario. The model is compared to Conti Scenario and observational data, showing good agreement with luminosity, effective temperature, and evolutionary phase, though not yet at final stages. This provides valuable insights into stellar evolution.